Teknik Relaksasi dan Exercise Intradialitik pada Pasien Hipotensi Intradialitik saat Menjalani Hemodialisis: A Case Study - Vina Vina; Masfuri Masfuri (Jurnal Penelitian Kesehatan SUARA FORIKES, 2021)
End-Stage Renal Disease is an end-stage chronic kidney disease and there is permanent loss of kidney function, so it requires routine hemodialysis throughout its life in order to survive. In undergoing hemodialysis can cause complications that arise that can affect the quality of life of patients, one of which is intradialytic hypotension. Nursing interventions were taken based on evidence from previous studies, namely the provision of intradialytic exercise and relaxation techniques. The purpose of this study was to analyze the effectiveness of giving intradialytic exercise and relaxation to the occurrence of intradialytic hypotension during dialysis. This study used a case analysis method which was carried out on one ESRD patient with intradialytic hypotension who was selected based on purposive sampling and was given intervention for 4 weeks in 12 hemodialysis sessions and immediately evaluated after each intervention. After giving intradialytic exercise intervention and relaxation techniques for 4 weeks, there were complaints of anxiety and the incidence of intradialitic hypotension decreased during the dialysis session. The provision of intradialytic exercise intervention and relaxation techniques can be recommended and implemented in treating patients with intradialytic hypotension because it is relatively easy and safe to implement in the hemodialysis unit. Keywords: end-stage renal disease; hemodialysis; intradialytic hypotension; intradialytic exercise; relaxation ABSTRAK End-Stage Renal Disease (ESRD) adalah suatu penyakit ginjal kronis stadium akhir dan terjadi kehilangan fungsi ginjal secara permanen sehingga memerlukan tindakan hemodialisis yang rutin disepanjang hidupnya agar dapat bertahan hidup. Dalam menjalani hemodialisis dapat menimbulkan komplikasi yang muncul sehingga dapat mempengaruhi kualitas hidup pasien salah satunya adalah hipotensi intradialitik. Intervensi keperawatan diambil berdasarkan bukti dari penelitian sebelumnya yaitu pemberian exercise intradialitik dan teknik relaksasi. Tujuan dari studi ini adalah menganalisis efektivitas pemberian exercise intradialitik dan relaksasi terhadap terjadinya hipotensi intradialitik selama menjalani dialisis. Studi ini menggunakan metode analisis kasus yang dilakukan pada satu pasien ESRD dengan hipotensi intradialitik yang dipilih berdasarkan purposive sampling dan diberikan intervensi selama 4 minggu dalam 12 kali sesi hemodialisis dan langsung dievaluasi setiap selesai pemberian intervensi. Setelah pemberian intervensi exercise intradialitik dan teknik relaksasi selama 4 minggu didapatkan keluhan kecemasan dan kejadian hipotensi intradialitikmengalami penurunan selama menjalani sesi dialysis. Pemberian intervensi exercise intradialitik dan teknik relaksasi ini dapat direkomendasikan dan diimplementasikan di dalam menanggani pasien dengan hipotensi intradialitik karena relatif mudah dan aman untuk diimplementasikan di unit hemodialisis. Kata kunci: end-stage renal disease; hemodialisis; hipotensi intradialitik; exercise intradialitik; relaksasi